A dilution method to increase the yield of engineered basic fibroblast growth factor - Widyantoro, Indira; Hirata, Isao; Kato, Koichi (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Genetically engineered chimeric proteins have potential applications as components of dental materials and can be synthesized recombinantly in various cells, including bacteria, yeast, insects and mammals. However, increasing the yields of functionally active products remains a challenge. Purpose: This study focused on basic fibroblast growth factor fused with pentadeca (GGGGS)3 peptide as a linker and hexahistidine as an affinity tag (bFGF-PH). The objective was to enhance the yield of bFGF-PH expressed in bacteria by employing a dilution method. Methods: Escherichia coli was used to express bFGF-PH in a soluble form, which was then purified using metal chelate affinity chromatography. The protein solution was diluted 100-fold with a buffer solution to promote spontaneous refolding. Subsequently, the protein solution was concentrated using metal chelate affinity chromatography. Circular dichroism (CD) spectroscopy was used to analyze the protein’s structure, assessing its correct folding by comparing it to a reference spectrum obtained through computer-based simulation. Results: The dilution method prevented bFGF-PH aggregation, and CD spectroscopy suggested that the protein was correctly folded. As a result, a total of 3.0 mg of bFGF-PH was obtained per liter of lysogeny broth medium, which was higher than the yield achieved using the conventional method. Conclusion: The dilution method examined in this study increased the yield of correctly folded bFGF-PH.